Kewenangan Pengelolaan Keuangan Lembaga Perkreditan Desa (LPD) Setelah Berlakunya Peraturan Daerah Nomor 29 Tahun 2013 - Made Ipunk Dwi Kusuma; Nyoman Putu Budiartha; Diah Gayatri Sudibya (Fakultas Hukum, Universitas Warmadewa, 2021)
The purpose of this research is to explain the authority of LPD financial management in Badung Regency, after the enactment of the Badung Regency Regulation No. 29/2013 and to find out the direction of the utilization of LPD coaching funds in Badung Regency. This research used normative legal research, with a statutory approach that specifically regulates the financial management authority of the LPD after the enactment of the Badung Regency Regulation number 29 of 2013. The data sources used were primary and secondary legal materials. The data were analyzed using descriptive qualitative method, namely the presentation by describing in detail certain aspects related to the problem being researched. The results showed that the authority to regulate the implementation of village credit institution activities in Badung Regency is still handled by the Provincial government because so far the Province has never handed over or delegated this authority to Badung Regency. Second, the utilization of village credit institution development funds is to provide guidance to LPDs in Bali and to improve the performance and quality of LPD management human resources.